PENGARUH LAYANAN BIMBINGAN KELOMPOK DENGAN METODE PROBLEM SOLVING UNTUK MENGURANGI CAREER INDECISION PADA SISWA SMA - Sari Rahayu; Yessy Elita; Vira Afriyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the high number of high school students experiencing career indecision. The purpose is to describe students' career indecision levels before and after receiving group guidance services with the problem solving method, and to examine the effect of these services among class XI.A students at SMA Negeri 6 Bengkulu City. A quantitative method with one-group pretest-posttest design was employed. Seven students were selected through purposive sampling based on high and very high career indecision criteria. The instrument was the Career Decision-Making Difficulties Questionnaire (CDDQ) with 30 Likert-scale items. Data were analyzed using paired sample t-test with SPSS. Results showed the mean career indecision score decreased from 113.14 (pre-test) to 72.00 (post-test), with t-value of 14.697 and significance of 0.000 (p < 0.05). It is concluded that group guidance services with the problem solving method significantly reduce career indecision in high school students.